Annual Plant Reviews Volume 43 2011
DOI: 10.1002/9781444339956.ch2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Analysis and Metabolomics in the Study of Biotrophic Interactions between Plants and Microbes

Abstract: Biotrophic plant-microbe interactions depend on the establishment of a nutritional interface allowing nutrient trafficking between plants and microbial symbionts and pathogens. A global re-programming of host and microbial metabolism is at the core of these interactions, and we summarise in this chapter studies on metabolome and, to add interpretational power, transcriptome changes associated with the establishment and maintenance of a range of plant-microbe associations. Pathogenic fungi of crops cause severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 197 publications
0
15
0
Order By: Relevance
“…Genotype x environment interaction is a topic of basic importance regarding how plants survive and function under what is normally an ever-changing environment (Ahuja et al, 2010;Browne et al, 2011;van Dam & van der Meijden, 2011). Furthermore, its importance in a crop production context enhances the value of this fundamental research (Browne et al, 2011;Draper et al, 2011). Metabolomics research has shown that changes in plant physiology, be they related to genetic or environmental perturbation, often involve widespread alteration in plant biochemistry not specifically restricted to particular pathways (Beale & Sussman, 2011).…”
Section: Metabolomics and Fundamental Plant Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Genotype x environment interaction is a topic of basic importance regarding how plants survive and function under what is normally an ever-changing environment (Ahuja et al, 2010;Browne et al, 2011;van Dam & van der Meijden, 2011). Furthermore, its importance in a crop production context enhances the value of this fundamental research (Browne et al, 2011;Draper et al, 2011). Metabolomics research has shown that changes in plant physiology, be they related to genetic or environmental perturbation, often involve widespread alteration in plant biochemistry not specifically restricted to particular pathways (Beale & Sussman, 2011).…”
Section: Metabolomics and Fundamental Plant Researchmentioning
confidence: 99%
“…These analyses are regularly focused specifically on aspects of product quality but metabolomics approaches are also regularly applied to tackle problems related to crop fitness involving disease resistance and its molecular basis, plant-insect interactions, mycorhizal interactions, stress effects, etc. (Ahuja et al, 2010;Draper et al, 2011). Through these approaches we are gradually gaining a much more detailed picture of crop biochemistry and its link to nutritional, sensory and other crop-related characteristics.…”
Section: Metabolomics and Applied Plant Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…We have not covered plant pathogen interactions as this topic has been covered extensively elsewhere (Draper et al, 2010). It is fair to say that care in the design of the experiment, sampling of tissue and collection of analytical data are fundamental.…”
Section: Forward Lookmentioning
confidence: 99%